PENINGKATAN KOMPETENSI GURU SD MELALUI PENGEMBANGAN MEDIA BELAJAR INTERAKTIF - Fawwaz, Muhammad Iqbal; Akbar, Muhammad Fikri; Churiyah, Madziatul; Sholikhan (Transpublika Publisher, 2022)
During this pandemic, teachers are required to be more creative and innovative in carrying out learning. It is still very rare for teachers to use the computer for the purpose of improving learning, let alone using Powerpoint-based learning media with various applications. Facts on the ground, namely in Cluster 6 Blimbing do not have sufficient competence in operating the tools available in Microsoft Office Powerpoint. Based on this, a learning media workshop is needed that is able to support this, does not require high specifications for laptop devices, and provides easy access guidebooks for educators. Powerpoint is an application that easily bridges users in designing various types of creative learning materials. In particular, PowerPoint has new features that can make it easier for educators to create media slides for presentations, learning videos, lesson plans, integration with virtual classroom platforms that support creativity and collaboration, etc. There are several specific activities that will be carried out to overcome the above problems through this Community Service, namely: 1) providing interactive learning media guidebooks to elementary school teachers; 2) holding a workshop “Development of Learning Media for Elementary School Teachers Using PowerPoint and Slidesgo”; and 3) Make a video tutorial